Frequency of Breast Abscess among Lactating Women Presenting to Ambulatory Care of Tertiary care Hospital - Siddique Ahmad, Sheema Amin, Muhammad Alam, Rizmi Tahir, Sarwat Noreen, Ali Gohar Khan, Amir Zareen, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The excruciating build-up of pus in breast tissue is known as a breast abscess. This condition is more common in lactating women and is caused by bacterial infection at the nipple zone, which is primarily brought on by biting the child while breastfeeding, poor sanitation, blockage of the milk ducts, and the development of lumps that may be cancerous. Mastitis to abscess development is at different levels of severity for breast abscesses. Breast abscesses can be central or perieolar in location. Acute cases are readily treatable, but surgical intervention is required for chronic cases. Aim: To determine the frequency of breast abscess among lactating women presenting to ambulatory care of tertiary care hospital of Peshawar. Study design: Cross-sectional observational study. Place and duration of study: Department of General Surgery, Hayatabad Medical Complex Peshawar from 1st March 2021 to 1st September 2021. Methodology: Three hundred and thirty four patients of ae groups 15–45 years old, lactating mothers up to 40 days after childbirth, and all women presenting with mastalgia (more than 3 on visual analogue scale) were included. Patients with an alternate infection site identified through clinical examination, those with diabetes (FBS >120mg/dl), those with other immunosuppressive conditions like HIV, and those with a history of steroid use within the previous month were excluded. Results: There were 49(14.7%) cases belong to age group of 19-30 years, while 31(9.3%) belongs to >30 years age (p 0.049). Thirty six (10.8%) of abscess was noted in those who had parity of 1-2 while 44(13.2%) had parity 3-4. The mean BMI of the study sample was 26.6+3.5kg/m2 amongst whom 29(8.7%) frequency of breast abscess was observed in 18.5-24.9 kg/m2, 36(10.8%) had BMI of 25-29.9 kg/m2 and 15(4.5%) had >30kg/m2. The mean postpartum day was 12.1±4.1 day. Fifty four (16.2%) abscess was noted in 6-12 postpartum day, while 26(7.8%) was noted in >12-19 postpartum day. Conclusion: Breast abscess was fairly common (24%) in postpartum women and significantly associated with age of the patient (>30 years). Keywords: Breast abscess, Parity, Lactating women, Post-partum, Body mass index